Identification of two SLI profiles through WISC-IV, CELF-4 and FON - Martínez, Ana B. (2015)
This work has two objectives. First of all, to offer psychometric instruments that help more precisely identify and differentiate children with specific language impairment (SLI) in the educational field and, secondly, to establish profiles of the two cases that illustrate the two current subtypes of SLI: phonologic-syntactic SLI and lexical-syntactic SLI. According to bibliographic reviews, the following tests are ideal for its identification: on the one hand the CELF-4, because language should be significantly the most affected area, the WISC – IV, an optimum test for the determination of the level of non-verbal reasoning, verbal comprehension, working memory and processing speed, and the FON, on a phonetic level, due to the level of analysis of the errors found. The results obtained in both cases corroborate a Perceptual Reasoning measured with WISC - IV, above 75, and the presence of a 1.5 deviation below average, in one of the three main scales of the CELF-4 (three in two cases: basic linguistic skills, receptive language and comprehensive language).